Peningkatan Hasil Belajar Permainan Voli Dengan Metode Variasi Di SMA Negeri 2 Siak Hulu - Yus Yetti (Universitas Lancang Kuning, 2022)
The issue is low learning results in volleyball games for students in SMA Negeri 2 Siak Hulu class XI Social Sciences. Most students can't pass over effectively and appropriately, and they're not interested in mastering passing over. Affects student learning outcomes This study aimed to improve the learning outcomes of passing over in volleyball games for SMA Negeri 2 Siak Hulu class XI IPS students. The study ran from July to October 2019. Classroom Action Research) with 59 students from class XI IPS, with 30 from class XI IPS.1 and 29 from class XI IPS.2. The data was collected through observation utilizing a volleyball passing skill test instrument. The results showed that using the variety approach in the volleyball game of passing learning activities increased passing learning outcomes for Class XI Social Sciences students by 72.88 percent in cycle 1, and 89.81 percent in cycle 2. good to excellent category This result suggests that students enjoy the material offered and desire to participate directly in learning since the material is enjoyable. Student engagement increased by 74.58 percent in cycle 1 and by 91.53 percent in cycle 2. Thus, the effective variation approach is employed in class XI IP SMA students to increase learning outcomes of passing over in volleyball.